Control and Utilization of Space at Hibisc Fantasy Puncak - Lidia Helena Indahsari Tobing (International Journal Multidisciplinary Science, 2026)
Spatial control and utilization are crucial aspects in realizing sustainable tourism development, particularly in highland areas with protected functions such as the Puncak area. This study aims to analyze spatial control and utilization in the Hibisc Fantasy Puncak tourist area in terms of its compliance with regional spatial plans, laws and regulations, and its impact on the environment and society of the surrounding community. The research method used is a descriptive qualitative approach through the study of policy documents, field observations, and interviews with relevant stakeholders. The results indicate that spatial utilization in Hibisc Fantasy Puncak is not fully aligned with the area's function, particularly regarding environmental carrying capacity and land conversion control. Weak supervision and enforcement of spatial planning regulations are the main factors causing the inconsistency in spatial utilization. Therefore, it is necessary to strengthen spatial control policies, improve inter-agency coordination, and implement sustainable development principles to maintain a balance between tourism development and environmental sustainability in the Puncak area.